Offshore wind turbine yaw brake pad and preparation method thereof

By using specific constituent materials and processes in the yaw braking pads of offshore wind turbines, the performance requirements of brake pads caused by wind shock during yaw braking of offshore wind power machines are solved, and the effects of high friction coefficient, corrosion resistance, low vibration and environmental protection are achieved.

CN116218133BActive Publication Date: 2025-03-07SHANXI JIANGHUAI HEAVY IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211533335.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-03-07
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

During the yaw braking process of offshore wind power machines, due to the excessive cutting wind force, the impact force on the blades is much greater than that of the land fan, resulting in the brake pads having good mechanical and frictional properties. At the same time, in special operating conditions at sea, the brake pads need to be corrosion-proof and low vibration to avoid adverse conditions such as noise and vibration.

Method used

It provides an offshore fan yaw brake pad whose dry friction coefficient is controlled between 0.40 and 0.45, has corrosion resistance, and the corrosion resistance level is RA-/10VSB, and there is no vibration and noise during braking. The brake pad consists of phenolic resin, friction powder, mineral fiber, ice crystal powder, aramid fiber, glass fiber, precipitated barium sulfate, scale graphite, pre-oxygen wire, rubber powder, molybdenum disulfide, tungsten disulfide and magnesium oxide, and is prepared by molding and three-stage heating and drying process.

Benefits of technology

The high and stable dry friction coefficient of the brake pad is achieved, which avoids adverse conditions such as noise and vibration during use, reduces the adverse effects on the fan foundation piles, and has environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116218133B_ABST
    Figure CN116218133B_ABST
Patent Text Reader

Abstract

The present invention proposes an offshore wind turbine yaw brake pad and a preparation method thereof, which belongs to the technical field of brake systems. The offshore wind turbine yaw brake pad comprises the following components in parts by weight: 10 to 18 parts of phenolic resin, 2 to 6 parts of friction powder, 15 to 25 parts of mineral fiber, 5 to 10 parts of cryolite powder, 3 to 6 parts of aramid fiber, 8 to 10 parts of glass fiber, 5 to 10 parts of precipitated barium sulfate, 3 to 8 parts of flake graphite, 7 to 12 parts of pre-oxidized wire, 2 to 4 parts of rubber powder, 2 to 5 parts of molybdenum disulfide, 5 to 10 parts of tungsten disulfide and 1 to 3 parts of magnesium oxide. The brake pad provided by the present invention has a dry friction coefficient between 0.40 and 0.45, and a corrosion resistance level of: R A ‑ / 10V S B. This brake pad is corrosion-resistant and low-vibration, which can avoid noise and vibration during use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of brake systems, and in particular relates to an offshore wind turbine yaw brake pad and a preparation method thereof. Background Art

[0002] Offshore wind power has the advantages of high wind speed, continuous and stable wind resources, and large power generation. However, due to the unique working conditions at sea, such as high salt and high humidity, strong winds have a strong impact on wind turbine blades and brake systems, and wind turbine foundation piles are installed on the seabed, higher requirements are placed on the quality of wind turbines, especially the quality of the brake system, among which the quality of the brake pads in the brake system is particularly important.

[0003] During the yaw braking process, the friction pads are subjected to a much greater impact force than land-based wind turbines due to the excessive wind force. This requires the yaw brake pads to not only have good mechanical and friction properties, but also to ensure that the brake pads have anti-corrosion and low vibration characteristics under the special working conditions at sea, so as to avoid noise and vibration during use, which would have an adverse effect on the wind turbine foundation piles. Therefore, providing high-performance brake pads has become an urgent need in the industry. Summary of the invention

[0004] In view of this, the present invention provides an offshore wind turbine yaw brake pad and a preparation method thereof, wherein the dry friction coefficient of the brake pad is between 0.40 and 0.45, and the brake pad has corrosion resistance, and the corrosion resistance level can reach R A - / 10V S B, and there is no vibration and noise during braking.

[0005] The present invention provides an offshore wind turbine yaw brake pad, comprising the following components in parts by weight: 10 to 18 parts of phenolic resin, 2 to 6 parts of friction powder, 15 to 25 parts of mineral fiber, 5 to 10 parts of cryolite powder, 3 to 6 parts of aramid fiber, 8 to 10 parts of glass fiber, 5 to 10 parts of precipitated barium sulfate, 3 to 8 parts of flake graphite, 7 to 12 parts of pre-oxidized wire, 2 to 5 parts of rubber powder, 2 to 5 parts of molybdenum disulfide, 5 to 10 parts of tungsten disulfide and 1 to 3 parts of magnesium oxide.

[0006] Preferably, the acetone extraction rate of the friction powder is ≤4.0% by weight; the ash content is ≤

[0007] 3.0; Thermal weight loss ≤30%.

[0008] Preferably, in terms of weight percentage, the free phenol content in the phenolic resin is ≤1.5%; the acrylonitrile content in the rubber powder is 35-40%; and the Mooney viscosity is 100-150M.

[0009] Preferably, the particle size of the phenolic resin is ≥200 mesh; the particle size of the friction powder is ≤30 mesh; the particle size of the rubber powder is 60-80 mesh; and the fiber lengths of the aramid fiber, mineral fiber, glass fiber and pre-oxidized fiber are independently 2-3 mm.

[0010] Preferably, the graphite content in the flake graphite is ≥95%.

[0011] Preferably, the magnesium content in the magnesium oxide is ≥98%.

[0012] Preferably, the dry friction coefficient of the brake pad is between 0.40 and 0.45, and the corrosion resistance level is: RA- / 10VSB.

[0013] The present invention also provides a method for preparing the offshore wind turbine yaw brake pad as described in any one of the above, comprising the following steps:

[0014] Mixing phenolic resin, friction powder, mineral fiber, cryolite powder, aramid fiber, glass fiber, precipitated barium sulfate, flake graphite, preoxidized silk, rubber powder, molybdenum disulfide, tungsten disulfide and magnesium oxide to obtain a mixed material;

[0015] The mixed material is molded and dried in sequence to obtain a brake pad.

[0016] Preferably, the compression molding conditions are: temperature 185-195°C, pressure 300-350 kg / mm 2 , holding time is 10 to 20 minutes.

[0017] Preferably, drying is carried out in a three-stage heating method, with the first heating to 138-142° C. and keeping warm for 1.8-2.2 hours; the second heating to 158-162° C. and keeping warm for 1.8-2.2 hours; and the third heating to 168-172° C. and keeping warm for 12-17 hours.

[0018] Compared with the prior art, the advantages and positive effects of the present invention are:

[0019] The present invention provides a brake pad, which controls the components and addition amount of the brake pad and cooperates with each other to control the dry friction coefficient of the brake pad between 0.40 and 0.45, and not only has a high friction coefficient, but also a stable friction coefficient, and also has the characteristics of low vibration and corrosion resistance, thereby avoiding noise, vibration and the like during use, which would have an adverse effect on the foundation pile of the wind turbine.

[0020] Furthermore, the present invention adopts organic fibers and inorganic fibers to replace metal fibers, thereby avoiding the use of metals and heavy metal compounds and being more environmentally friendly.

[0021] Furthermore, the present invention provides a method for preparing the brake pad, which is formed by molding and dried by a three-stage heating method, which not only saves energy but also makes the performance of the brake pad more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the installation diagram of the BSY-120 yaw brake comprehensive test bench. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The present invention provides an offshore wind turbine yaw brake pad, comprising the following components in parts by weight: 10 to 18 parts of phenolic resin, 2 to 6 parts of friction powder, 15 to 25 parts of mineral fiber, 5 to 10 parts of cryolite powder, 3 to 6 parts of aramid fiber, 8 to 10 parts of glass fiber, 5 to 10 parts of precipitated barium sulfate, 3 to 8 parts of flake graphite, 7 to 12 parts of pre-oxidized wire, 2 to 5 parts of rubber powder, 2 to 5 parts of molybdenum disulfide, 5 to 10 parts of tungsten disulfide and 1 to 3 parts of magnesium oxide.

[0025] The offshore wind turbine yaw brake pad provided by the present invention includes phenolic resin, which includes 10 to 18 parts by weight, preferably 13 to 15 parts. In the present invention, the free phenol content in the phenolic resin is ≤1.5% by weight percentage; the fluidity of the phenolic resin is preferably 33 to 45 mm; the polymerization speed at 150°C is preferably: 70 to 90s, and the moisture content is ≤1.7%. In the present invention, the particle size of the phenolic resin is preferably ≥200 mesh, more preferably 300 mesh. In the present invention, the phenolic resin not only has a bonding effect, bonding the various fiber components together, but also enables them to better play their respective roles, and plays a key role in the ductility and impact strength of the composite material.

[0026] The offshore wind turbine yaw brake pad provided by the present invention includes friction powder, which includes 2 to 6 parts by weight, preferably 3 to 5 parts. In the present invention, preferably, by weight percentage, the acetone extraction rate of the friction powder is ≤4.0%; the ash content is ≤3.0; and the thermal weight loss is ≤30%. In the present invention, the particle size of the friction powder is preferably ≤30 mesh, more preferably 20 mesh. In the present invention, the addition of friction powder reduces the elastic modulus of the friction material, and the friction coefficient is more stable, which not only improves the braking effect, but also greatly reduces the aggressiveness to the pair.

[0027] The offshore wind turbine yaw brake pad provided by the present invention includes mineral fibers, which include 15 to 25 parts by weight, preferably 16 to 20 parts. In the present invention, the mineral fibers preferably include silicon dioxide, sepiolite, and wollastonite. In the present invention, the fiber length of the mineral fibers is preferably 2 to 3 mm. The mineral fibers in the present invention bear more than two-thirds of the load in the material and provide the material with properties such as hardness, strength and thermal stability.

[0028] The offshore wind turbine yaw brake pad provided by the present invention includes 5 to 10 parts by weight of cryolite powder, preferably 7 to 9 parts. In the present invention, the particle size of the cryolite powder is preferably 300 to 400 meshes. In the present invention, the cryolite powder plays a role in reducing the hardness of the friction material and improving the wear resistance.

[0029] The offshore wind turbine yaw brake pad provided by the present invention includes 8 to 10 parts by weight, preferably 9 to 9.5 parts by weight of glass fiber. In the present invention, the fiber length of the glass fiber is preferably 2 to 3 mm. In the present invention, the glass fiber not only has excellent thermal insulation and electrical insulation properties, is not affected by moisture, but also is stable in general weak acid, alkali and other chemical environments, and can also improve the strength of the friction material.

[0030] The offshore wind turbine yaw brake pad provided by the present invention includes 5 to 10 parts by weight of precipitated barium sulfate, preferably 6 to 8 parts. In the present invention, the precipitated barium sulfate can better stabilize the friction coefficient, reduce the wear rate, and the friction surface is smooth and clean, greatly reducing the wear debris on the friction surface.

[0031] The offshore wind turbine yaw brake pad provided by the present invention includes 7 to 12 parts by weight, preferably 8 to 10 parts by weight of pre-oxidized yarn. In the present invention, the fiber length of the pre-oxidized yarn is preferably 2 to 3 mm. In the present invention, the pre-oxidized yarn not only has excellent high temperature resistance and stabilizes the friction coefficient of the friction material at high temperature, but also improves the strength of the material while reducing the wear rate.

[0032] The offshore wind turbine yaw brake pad provided by the present invention includes 3 to 8 parts by weight, preferably 4 to 6 parts of flake graphite. In the present invention, the graphite content in the flake graphite is preferably ≥ 95% by weight. In the present invention, the flake graphite can significantly stabilize the friction coefficient, maintain a stable braking process, and reduce dual surface damage and vibration noise.

[0033] The offshore wind turbine yaw brake pad provided by the present invention includes rubber powder, which includes 2 to 5 parts by weight, preferably 2.5 to 3 parts. In the present invention, the acrylonitrile content in the rubber powder is preferably 35 to 40% by weight; the Mooney viscosity is preferably 100 to 150M. In the present invention, the rubber powder is preferably nitrile rubber powder. In the present invention, the particle size of the rubber powder is preferably 60 to 80 meshes. In the present invention, the rubber powder can effectively improve the mechanical properties of phenolic resin, so that the product has good toughness and elasticity, and the braking is smooth without vibration and noise.

[0034] The offshore wind turbine yaw brake pad provided by the present invention comprises 2 to 5 parts by weight, preferably 2.2 to 3.2 parts by weight of molybdenum disulfide. In the present invention, the molybdenum disulfide has a good friction reduction effect in the low temperature range and can cover the surface of the friction material to play an anti-oxidation function.

[0035] The offshore wind turbine yaw brake pad provided by the present invention comprises tungsten disulfide, which comprises 5 to 10 parts by weight, preferably 6 to 9 parts by weight. In the present invention, the tungsten disulfide is used as a solid lubricant to provide good anti-wear performance for the friction material.

[0036] The offshore wind turbine yaw brake pad provided by the present invention includes magnesium oxide, which includes 1 to 3 parts by weight, preferably 1.5 to 2.7 parts. In the present invention, the purity of the magnesium oxide is above 98% by weight. In the present invention, magnesium oxide is used as a resin curing catalyst to effectively improve the density of the friction material and reduce thermal decay.

[0037] In the present invention, the offshore wind turbine yaw brake pad is an active brake pad, which has a braking effect. As an active brake pad, it is not only required to have a high dry friction coefficient (dry friction: friction in the atmosphere) to achieve a rapid braking effect, but also to have a stable friction coefficient in order to ensure a smooth braking process and reduce vibration and noise. In the offshore wind turbine yaw brake pad provided by the present invention, phenolic resin is used as a binder to bond other components together so that they have sufficient ductility and impact strength. Rubber powder is combined with phenolic resin to optimize the mechanical properties of the friction material, making the braking process more stable and vibration-free. The good high temperature resistance of the pre-oxidized wire provides a stable high temperature friction coefficient for the friction material. The friction reduction effect of molybdenum disulfide in the low temperature section forms a protective film on the surface to prevent material oxidation. The good lubrication properties of flake graphite and tungsten disulfide stabilize the friction coefficient and protect the pair from being damaged, while effectively suppressing vibration noise and low wear rate. The friction powder reduces the elastic modulus of the friction material and greatly reduces the aggressiveness to the pair. The glass fiber has good high temperature and humidity resistance, and is stable in some specific chemical environments, while providing a certain strength for the friction material. It can be understood that the present invention controls the components and addition amount of the wind turbine yaw brake pad, and through the joint action of each component, the brake pad has corrosion resistance, low vibration, and a high and stable dry friction coefficient.

[0038] The present invention has no special restrictions on the specific sources of the phenolic resin, friction powder, mineral fiber, cryolite powder, aramid fiber, glass fiber, precipitated barium sulfate, flake graphite, pre-oxidized wire, rubber powder, molybdenum disulfide, tungsten disulfide and magnesium oxide, and conventional commercial products in the field can be used.

[0039] The present invention also provides a method for preparing the offshore wind turbine yaw brake pad according to any one of the above solutions, comprising the following steps:

[0040] Mixing phenolic resin, friction powder, mineral fiber, cryolite powder, aramid fiber, glass fiber, precipitated barium sulfate, flake graphite, preoxidized silk, rubber powder, molybdenum disulfide, tungsten disulfide and magnesium oxide to obtain a mixed material;

[0041] The mixed material is molded and dried in sequence to obtain a brake pad.

[0042] Phenolic resin, friction powder, mineral fiber, cryolite powder, aramid fiber, glass fiber, precipitated barium sulfate, flake graphite, preoxidized wire, rubber powder, molybdenum disulfide, tungsten disulfide and magnesium oxide are mixed to obtain a mixed material. In the present invention, the mixing method is preferably stirring. The stirring time is preferably 3 to 5 minutes, more preferably 4 minutes. The stirring speed is preferably 1400 to 1600 r / min, more preferably 1500 r / min. In the present invention, a high-speed mixer dedicated to friction materials is preferably used for mixing.

[0043] After obtaining the mixed material, the present invention sequentially molds and dries the mixed material to obtain a brake pad. In the present invention, the molding conditions are preferably: a temperature of 185-195°C and a pressure of 300-350 kg / mm 2 , holding time is 10 to 20 minutes.

[0044] In the present invention, it is preferred to use a three-stage heating method for drying, the first heating to 138-142°C, keeping warm for 1.8-2.2h; the second heating to 158-162°C, keeping warm for 1.8-2.2h; the third heating to 168-172°C, keeping warm for 12-17h, more preferably the first heating to 140°C, keeping warm for 2h; the second heating to 160°C, keeping warm for 2h; the third heating to 170°C, keeping warm for 14h. In the present invention, the first heating removes moisture; the second heating to a medium temperature allows the resin to be basically cured; the third heating to a high temperature allows the resin to be completely cured. The present invention uses a three-stage heating method for drying, which saves energy consumption and can make the performance of the brake pad more stable.

[0045] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0046] The specific sources of the components in the embodiment are as follows:

[0047] The phenolic resin is PF-6816 produced by Shandong Shengquan New Materials Co., Ltd.; the friction powder is model NX-2020-30 produced by Hangzhou Shanhai Chemical Technology Co., Ltd.; the cryolite powder is model T300 produced by Huangshi Xinyi New Materials Technology Co., Ltd.; the glass fiber manufacturer is Danyang Zhenxing Glass Fiber Co., Ltd.; precipitated barium sulfate: Zhushan Qinba Barium Salt Co., Ltd.; tungsten disulfide: Huajing Powder Material Co., Ltd.; flake graphite: Qingdao Jintao Graphite Co., Ltd.; rubber powder model N-IS produced by Nanjing Xinfeima Chemical Co., Ltd.; molybdenum disulfide: Jinduicheng Molybdenum Industry Trading Co., Ltd.; magnesium oxide: Hebei Gaolin Magnesium Salt Chemical Co., Ltd.; pre-oxidized wire is produced by Changzhou Saibang New Material Technology Co., Ltd.

[0048] Example 1

[0049] The formula of the brake pad is: 13.5kg phenolic resin, 4kg friction powder, 16kg mineral fiber (sepiolite), 7kg cryolite powder, 3kg aramid fiber, 9.5kg glass fiber, 7.6kg precipitated barium sulfate, 4kg flake graphite, 4.8kg rubber powder, 7.7kg pre-oxidized silk, 2.2kg molybdenum disulfide, 9.2kg tungsten disulfide, and 2.6kg magnesium oxide.

[0050] Among them: the particle size of phenolic resin is 200 mesh; the particle size of friction powder is 20 mesh; the fiber length of mineral fiber is 2.8mm; the fiber length of aramid fiber is 2.6mm; the fiber length of glass fiber is 3mm; the fiber length of pre-oxidized yarn is 2.5mm; the mass percentage content of graphite in flake graphite is 95%; the particle size of rubber powder is 60-80 mesh; the purity of magnesium oxide is 98%.

[0051] (1) Weigh the components according to the above formula, put the weighed materials into a special high-speed mixer for friction materials and mix them at a speed of 1500 r / min for 3.5 minutes.

[0052] (2) Compression molding: The obtained mixed material is placed in a mold for compression molding at a mold temperature of 190°C and a pressure of 300 kg / mm 2 , holding time is 20min, and the brake pad semi-finished product is obtained.

[0053] (3) The semi-finished brake pad obtained in step (2) is placed in an oven, heated to 140°C for the first time and kept warm for 2 hours; heated to 160°C for the second time and kept warm for 2 hours; heated to 170°C for the third time and kept warm for 12 hours to obtain a finished brake pad.

[0054] Example 2

[0055] The formula of the brake pad is: 14.5kg phenolic resin, 3kg friction powder, 17kg mineral fiber (sepiolite), 7kg cryolite powder, 4kg aramid fiber, 9.5kg glass fiber, 8kg precipitated barium sulfate, 5kg flake graphite, 4.8kg rubber powder, 8.6kg pre-oxidized silk, 2.2kg molybdenum disulfide, 5.2kg tungsten disulfide, and 2kg magnesium oxide.

[0056] Among them: the particle size of phenolic resin is 200 mesh; the particle size of friction powder is 20 mesh; the fiber length of mineral fiber is 2-3 mm; the fiber length of aramid fiber is 2-3 mm; the fiber length of glass fiber is 2-3 mm; the fiber length of pre-oxidized yarn is 2-3 mm; the mass percentage content of graphite in flake graphite is 95%; the particle size of rubber powder is 60-80 mesh; the purity of magnesium oxide is 98%.

[0057] (1) Weigh the components according to the above formula, put the weighed materials into a special high-speed mixer for friction materials and mix them at a speed of 1500 r / min for 3.5 minutes.

[0058] (2) Compression molding: The obtained mixed material is placed in a mold for compression molding at a mold temperature of 190°C and a pressure of 300 kg / mm 2 , holding time is 20min, and the brake pad semi-finished product is obtained.

[0059] (3) The semi-finished brake pad obtained in step (2) is placed in an oven, heated to 140°C for the first time and kept warm for 2 hours; heated to 160°C for the second time and kept warm for 2 hours; heated to 170°C for the third time and kept warm for 12 hours to obtain a finished brake pad.

[0060] Example 3

[0061] The formula of the brake pad is: 14.5kg phenolic resin, 6kg friction powder, 15kg mineral fiber (silicon dioxide), 9kg cryolite powder, 5kg aramid fiber, 8.5kg glass fiber, 5kg precipitated barium sulfate, 8kg flake graphite, 3kg rubber powder, 10kg pre-oxidized wire, 3.2kg molybdenum disulfide, 6.2kg tungsten disulfide, and 1kg magnesium oxide.

[0062] Among them: the particle size of phenolic resin is 200 mesh; the particle size of friction powder is 20 mesh; the fiber length of mineral fiber is 2-3 mm; the fiber length of aramid fiber is 2-3 mm; the fiber length of glass fiber is 2-3 mm; the fiber length of pre-oxidized yarn is 2-3 mm; the mass percentage content of graphite in flake graphite is 95%; the particle size of rubber powder is 60-80 mesh; the purity of magnesium oxide is 98%.

[0063] (1) Weigh the components according to the above formula, put the weighed materials into a special high-speed mixer for friction materials and mix them at a speed of 1500 r / min for 3.5 minutes.

[0064] (2) Compression molding: The obtained mixed material is placed in a mold for compression molding at a mold temperature of 190°C and a pressure of 300 kg / mm 2 , holding time is 20min, and the brake pad semi-finished product is obtained.

[0065] (3) The semi-finished brake pad obtained in step (2) is placed in an oven, heated to 140°C for the first time and kept warm for 2 hours; heated to 160°C for the second time and kept warm for 2 hours; heated to 170°C for the third time and kept warm for 12 hours to obtain a finished brake pad.

[0066] Example 4

[0067] The formula of the brake pad is: 18kg phenolic resin, 2kg friction powder, 25kg mineral fiber (sepiolite), 9kg cryolite powder, 6kg aramid fiber, 8.5kg glass fiber, 10kg precipitated barium sulfate, 8kg flake graphite, 4kg rubber powder, 12kg pre-oxidized wire, 3.2kg molybdenum disulfide, 6.2kg tungsten disulfide, and 3kg magnesium oxide.

[0068] Among them: the particle size of phenolic resin is 200 mesh; the particle size of friction powder is 20 mesh; the fiber length of mineral fiber is 2-3 mm; the fiber length of aramid fiber is 2-3 mm; the fiber length of glass fiber is 2-3 mm; the fiber length of pre-oxidized yarn is 2-3 mm; the mass percentage content of graphite in flake graphite is 95%; the particle size of rubber powder is 60-80 mesh; the purity of magnesium oxide is 98%.

[0069] (1) Weigh the components according to the above formula, put the weighed materials into a special high-speed mixer for friction materials and mix them at a speed of 1500 r / min for 3.5 minutes.

[0070] (2) Compression molding: The obtained mixed material is placed in a mold for compression molding at a mold temperature of 190°C and a pressure of 300 kg / mm 2 , holding time is 20min, and the brake pad semi-finished product is obtained.

[0071] (3) The semi-finished brake pad obtained in step (2) is placed in an oven, heated to 140°C for the first time and kept warm for 2 hours; heated to 160°C for the second time and kept warm for 2 hours; heated to 170°C for the third time and kept warm for 12 hours to obtain a finished brake pad.

[0072] Comparative Example 1

[0073] The preparation method is the same as that of Example 1, except that the content of phenolic resin is 20 kg.

[0074] The specific formula is: 20kg phenolic resin, 4kg friction powder, 16kg mineral fiber (sepiolite), 7kg cryolite powder, 3kg aramid fiber, 9.5kg glass fiber, 7.6kg precipitated barium sulfate, 4kg flake graphite, 4.8kg rubber powder, 7.7kg pre-oxidized wire, 2.2kg molybdenum disulfide, 9.2kg tungsten disulfide, and 2.6kg magnesium oxide.

[0075] Comparative Example 2

[0076] The preparation method is the same as that of Example 1, except that the content of cryolite powder is 15 kg.

[0077] The specific formula is: 13.5kg phenolic resin, 4kg friction powder, 16kg mineral fiber (sepiolite), 15kg cryolite powder, 3kg aramid fiber, 9.5kg glass fiber, 7.6kg precipitated barium sulfate, 4kg flake graphite, 4.8kg rubber powder, 7.7kg pre-oxidized silk, 2.2kg molybdenum disulfide, 9.2kg tungsten disulfide, and 2.6kg magnesium oxide.

[0078] Comparative Example 3

[0079] The preparation method is the same as that of Example 1, except that the content of tungsten disulfide is 15 kg.

[0080] The specific formula is: 13.5kg phenolic resin, 4kg friction powder, 16kg mineral fiber (sepiolite), 7kg cryolite powder, 3kg aramid fiber, 9.5kg glass fiber, 7.6kg precipitated barium sulfate, 4kg flake graphite, 4.8kg rubber powder, 7.7kg pre-oxidized wire, 2.2kg molybdenum disulfide, 15kg tungsten disulfide, and 2.6kg magnesium oxide.

[0081] Comparative Example 4

[0082] The preparation method is the same as that of Example 1, except that no rubber powder is added.

[0083] The specific formula is: 13.5kg phenolic resin, 4kg friction powder, 16kg mineral fiber (sepiolite), 7kg cryolite powder, 3kg aramid fiber, 9.5kg glass fiber, 7.6kg precipitated barium sulfate, 4kg flake graphite, 7.7kg pre-oxidized wire, 2.2kg molybdenum disulfide, 9.2kg tungsten disulfide, and 2.6kg magnesium oxide.

[0084] Comparative Example 5

[0085] The preparation method is the same as that of Example 1, except that molybdenum disulfide is not added.

[0086] 13.5kg phenolic resin, 4kg friction powder, 16kg mineral fiber, 7kg cryolite powder, 3kg aramid fiber, 9.5kg glass fiber, 7.6kg precipitated barium sulfate, 4kg flake graphite, 4.8kg rubber powder, 7.7kg pre-oxidized wire, 9.2kg tungsten disulfide, and 2.6kg magnesium oxide.

[0087] Comparative Example 6

[0088] The preparation method is the same as that of Example 1, except that no pre-oxidized fiber is added.

[0089] 13.5kg phenolic resin, 4kg friction powder, 16kg mineral fiber (sepiolite), 7kg cryolite powder, 3kg aramid fiber, 9.5kg glass fiber, 7.6kg precipitated barium sulfate, 4kg flake graphite, 4.8kg rubber powder, 2.2kg molybdenum disulfide, 9.2kg tungsten disulfide, and 2.6kg magnesium oxide.

[0090] Comparative Example 7

[0091] The preparation method is the same as that of Example 1, except that the calcium sulfate whiskers are replaced by precipitated barium sulfate.

[0092] 13.5kg phenolic resin, 4kg friction powder, 16kg mineral fiber (sepiolite), 7kg cryolite powder, 3kg aramid fiber, 9.5kg glass fiber, 7.6kg calcium sulfate whisker, 4kg flake graphite, 4.8kg rubber powder, 7.7kg pre-oxidized wire, 2.2kg molybdenum disulfide, 9.2kg tungsten disulfide, and 2.6kg magnesium oxide.

[0093] Comparative Example 8

[0094] The specific formula is: 18.5kg phenolic resin, 1.6kg friction enhancer (silicon dioxide), 7.5kg carbon fiber, 10kg basalt fiber, 3.5kg aramid pulp, 10kg glass fiber, 5kg cellulose fiber, 9.6kg flake graphite, 5kg rubber powder, 7.5kg molybdenum disulfide, 9.2kg tungsten disulfide, 3kg magnesium oxide, and 9.6kg calcium sulfate whiskers.

[0095] Comparative Example 9

[0096] Except for the heat treatment process in step (3) of the preparation method, the other operation steps are exactly the same as those in Example 1.

[0097] The formula of the brake pad is: 13.5kg phenolic resin, 4kg friction powder, 16kg mineral fiber (sepiolite), 7kg cryolite powder, 3kg aramid fiber, 9.5kg glass fiber, 7.6kg precipitated barium sulfate, 4kg flake graphite, 4.8kg rubber powder, 7.7kg pre-oxidized silk, 2.2kg molybdenum disulfide, 9.2kg tungsten disulfide, and 2.6kg magnesium oxide.

[0098] Among them: the particle size of phenolic resin is 200 mesh; the particle size of friction powder is 20 mesh; the fiber length of mineral fiber is 2-3 mm; the fiber length of aramid fiber is 2-3 mm; the fiber length of glass fiber is 2-3 mm; the fiber length of pre-oxidized yarn is 2-3 mm; the mass percentage content of graphite in flake graphite is 95%; the particle size of rubber powder is 60-80 mesh; the purity of magnesium oxide is 98%.

[0099] (1) Weigh the components according to the above formula, put the weighed materials into a special high-speed mixer for friction materials and mix them at a speed of 1500 r / min for 3.5 minutes.

[0100] (2) Compression molding: The obtained mixed material is placed in a mold for compression molding at a mold temperature of 190°C and a pressure of 300 kg / mm 2 , holding time is 20min, and the brake pad semi-finished product is obtained.

[0101] (3) The semi-finished brake pad obtained in step (2) is placed in an oven, heated to 170° C., and kept warm for 12 hours to obtain a finished brake pad.

[0102] Performance Testing

[0103] The performance of the brake pads prepared in Examples 1 to 4 and Comparative Examples 1 to 9 were tested respectively, and the specific results are shown in Table 1.

[0104] Table 1 Performance test results of brake pads

[0105]

[0106]

[0107] The friction performance test was carried out in accordance with the "BSY-120 Yaw Brake Type Test Outline A09"; the corrosion resistance test was carried out in accordance with the neutral salt spray test method specified in the standard GB / T 10125 "Artificial Atmosphere Corrosion Test Salt Spray Test". After 240 hours of testing, it met the requirements of RA- / 10VSB in GB / T 6461 "Rating of Test Specimens and Specimens after Corrosion Tests of Metallic and Other Inorganic Coatings on Metallic Substrates", and the final corrosion appearance rating was "None".

[0108] Note: The test method of "BSY-120 Yaw Brake Type Test Outline A09" is as follows:

[0109] The pad wear performance test of the brake friction pad is tested on a yaw brake comprehensive test bench (such as Figure 1 ). Before the test, measure and record the mass and thickness of the brake friction pad to be tested. Make the simulated brake disc reciprocate under the brake clamping state. After pushing and pulling a certain number of times, remove the brake pad to measure and record its mass and thickness. Then calculate the wear amount by calculating the thickness difference of the brake pad before and after the test.

[0110] 1. Pad friction coefficient test

[0111] The pad wear coefficient test of the brake friction pad is tested on a yaw brake comprehensive test bench (such as Figure 1 ).

[0112] 1.1 Pressure holding test

[0113] The brake is connected to the pipeline on the comprehensive test bench, the oil pressure is 160 bar, the pressure is maintained for 10 minutes, and the caliper body interface connection pipeline and other locations are checked for oil leakage.

[0114] 1.2 Friction coefficient test during the running-in period

[0115] The friction coefficient determination contents during the running-in period are shown in Table 2

[0116] Table 2 Friction coefficient determination content during running-in period

[0117]

[0118] Repeat the test items in Table 2 until the friction coefficient is stable. Save and record the friction coefficient and curve during the test. If the surface temperature of the mating parts is greater than +60℃ during the test, stop and continue the test after the temperature is lower than +45℃.

[0119] 1.3 Friction coefficient test during stable period

[0120] The content of the friction coefficient determination during the running-in period is shown in Table 3. Measure and record 5 sets of data again. If the surface temperature of the mating parts is greater than +60°C during the process, stop and continue the test after the temperature is lower than +45°C.

[0121] Table 3 Determination of friction coefficient in stable period

[0122]

[0123] 2. Brake pad noise detection

[0124] Install the brake pad to be tested on the test bench (such as Figure 1 ). A constant oil pressure is applied to the brake through the control system. The brake will be in a braking state under the action of the oil pressure and clamp the simulated brake disc; then the pressure oil is input into the push cylinder to drive the simulated brake disc (brake plate) to do reciprocating motion. The control system collects the test data in real time, calculates it, and outputs the calculation results to obtain the friction coefficient value of the brake friction pad. At the same time, a noise meter is used at a distance of 1 meter from the product to collect the braking noise during the test. Noise and screaming are recorded as soon as they occur. Vibration below 70db is recorded as no vibration, vibration between 70db-80db is recorded as slight vibration, and vibration above 80db is recorded as strong vibration.

[0125] 3. Water induction test

[0126] 3.1 Install the brake and friction plate on the yaw simulation test platform.

[0127] 3.2 Spray an appropriate amount of water on the upper and lower surfaces of the yaw brake plate and start the yaw movement. The requirements are shown in Table 4.

[0128] Table 4 Requirements for water induction test

[0129]

[0130] 4. Grease induction test

[0131] 4.1 Clean the friction plate and brake plate and keep the friction surfaces dry and clean;

[0132] 4.2 Set the oil pressure to 30 bar, the yaw speed to 5 mm / S, and start yaw. When the decibel meter value is close to that before the water induction test, you can stop:

[0133] 4.3 When the yaw stops, apply a proper amount of grease on the upper surface of the brake plate and start the yaw movement. The requirements are shown in Table 5:

[0134] Table 5 Grease induction test requirements

[0135]

[0136] 5. Hydraulic oil induction test

[0137] Clean the friction plate and brake plate, and keep the friction surfaces dry and clean; set the oil pressure to 30 bar, the yaw speed to 5 mm / S, and start yaw. Stop when the decibel meter value is close to that before the water induction test:

[0138] When the yaw stops, apply a proper amount of hydraulic oil on the upper surface of the brake plate and start the yaw movement. The requirements are shown in Table 6:

[0139] Table 6 Hydraulic oil induction test requirements

[0140]

[0141] It can be seen from Table 1 that the dry friction coefficient of the brake pad provided by the present invention is between 0.40 and 0.45, the friction coefficient is high and stable, and no abnormal phenomenon occurs under the working conditions of high temperature +70°C and low temperature -40°C. The excellent corrosion resistance can meet the requirements of stable and normal operation in the high-salt, high-humidity and high-temperature marine environment, and at the same time has the advantages of low wear rate and long service life.

[0142] Note: 1. The dry friction coefficient is determined based on the test number 4 in Table 3 (pressure 30 bar; speed 14 mm / s; measurement stroke 50 m), and the average friction coefficient value after measuring 5 groups in total.

[0143] 2. The wet friction coefficient is determined based on the test number 5 in Table 6 (water spraying is the entire upper and lower planes of the dual parts; pressure 30 bar; speed 5 mm / s; stroke 6 m), and the average friction coefficient after 5 groups is measured.

[0144] 3. High temperature friction and low temperature friction are measured according to the test number 4 in Table 3 (pressure 30 bar; speed 14 mm / s; measurement stroke 50 m; high temperature +70°C; low temperature -40°C), and the average friction coefficient value after 5 groups is measured.

[0145] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An offshore wind turbine yaw brake pad, characterized in that: The invention comprises the following components in parts by weight: 10-18 parts of phenolic resin, 2-6 parts of friction powder, 15-25 parts of mineral fiber, 5-10 parts of cryolite powder, 3-6 parts of aramid fiber, 8-10 parts of glass fiber, 5-10 parts of precipitated barium sulfate, 3-8 parts of flake graphite, 7-12 parts of preoxidized wire, 2-5 parts of rubber powder, 2-5 parts of molybdenum disulfide, 5-10 parts of tungsten disulfide and 1-3 parts of magnesium oxide; The friction powder is a friction powder of model NX-2020-30 produced by Hangzhou Shanhai Chemical Technology Co., Ltd. The method for preparing the offshore wind turbine yaw brake pad comprises the following steps: Mixing phenolic resin, friction powder, mineral fiber, cryolite powder, aramid fiber, glass fiber, precipitated barium sulfate, flake graphite, preoxidized silk, rubber powder, molybdenum disulfide, tungsten disulfide and magnesium oxide to obtain a mixed material; The mixed material is sequentially molded and dried to obtain a brake pad; Among them, a three-stage heating method is adopted for drying. The first temperature is raised to 138~142℃ and kept warm for 1.8~2.2h; the second temperature is raised to 158~162℃ and kept warm for 1.8~2.2h; the third temperature is raised to 168~172℃ and kept warm for 12~17h.

2. The brake pad according to claim 1, characterized in that Calculated by weight percentage, the free phenol content in the phenolic resin is ≤1.5%; the acrylonitrile content in the rubber powder is 35-40%; and the Mooney viscosity is 100-150M.

3. The brake pad according to claim 1, characterized in that The particle size of the phenolic resin is ≥200 mesh; the particle size of the friction powder is ≤30 mesh; the particle size of the rubber powder is 60-80 mesh; the fiber lengths of the aramid fiber, mineral fiber, glass fiber and pre-oxidized fiber are independently 2-3 mm.

4. The brake pad according to claim 1, characterized in that Measured by mass percentage, the graphite content in the flake graphite is ≥95%.

5. The brake pad according to claim 1, characterized in that Measured by mass percentage, the purity of the magnesium oxide is ≥98%.

6. The brake pad according to claim 1, characterized in that The dry friction coefficient of the brake pad is between 0.40 and 0.45, and the corrosion resistance level is: RA- / 10VSB.

7. The method for preparing the offshore wind turbine yaw brake pad according to any one of claims 1 to 6, characterized in that: The steps include: Mixing phenolic resin, friction powder, mineral fiber, cryolite powder, aramid fiber, glass fiber, precipitated barium sulfate, flake graphite, preoxidized silk, rubber powder, molybdenum disulfide, tungsten disulfide and magnesium oxide to obtain a mixed material; The mixed material is molded and dried in sequence to obtain a brake pad.

8. The preparation method according to claim 7, characterized in that: The compression molding conditions are: temperature 185-195°C, pressure 300-350 kg / mm 2 , holding time is 10~20min.

9. The preparation method according to claim 7, characterized in that: The drying is carried out in a three-stage heating method. The first heating is heated to 138~142℃ and kept warm for 1.8~2.2h; the second heating is heated to 158~162℃ and kept warm for 1.8~2.2h; the third heating is heated to 168~172℃ and kept warm for 12~17h.

Citation Information

Patent Citations

  • Friction material composition and friction material for preparing brake pad

    CN101613516A

  • Synthetic abrasive material with ground dust as main body and friction material

    CN102977849A